Cost optimal scenarios of a future highly renewable European electricity system: Exploring the influence of weather data, cost parameters and policy constraints. (15th November 2018) - Schlachtberger, D.P.; Brown, T.; Schäfer, M.; Schramm, S.; Greiner, M.
Abstract: Cost optimal scenarios derived from models of a highly renewable electricity system depend on the specific input data, cost assumptions and system constraints. Here this influence is studied using a techno-economic optimisation model for a networked system of 30 European countries, taking into account the capacity investment and operation of wind, solar, hydroelectricity, natural gas power generation, transmission, and different storage options. A considerable robustness of total system costs to the input weather data and to moderate changes in the cost assumptions is observed. Flat directions in the optimisation landscape around cost-optimal configurations often allow system planners to choose between different technology options without a significant increase in total costs, for instance by replacing onshore with offshore wind power capacity in case of public acceptance issues. Exploring a range of carbon dioxide emission limits shows that for scenarios with moderate transmission expansion, a reduction of around 57% compared to 1990 levels is already cost optimal. For stricter carbon dioxide limits, power generated from gas turbines is at first replaced by generation from increasing renewable capacities. Non-hydro storage capacities are only built for low-emission scenarios, in order to provide the necessary flexibility to meet peaks in the residual load. Highlights: Influence of input data and assumptions for a highly-renewable scenario are studied. System costs are robust to input weather data and moderate cost assumption changes. Onshore wind can be replaced by offshore at low cost if there is enough national transmission. As carbon dioxide limits are tightened, costs rise only slowly if there is grid capacity. Storage is economic above 80% renewables; without storage 99.9% is possible, but costs double.